As interseções midiáticas da pequena Bom Sucesso de 1938-1954: leituras e discursos de Júlio Castanheira - Rodrigo Vivas Andrade (2001)
Júlio Castanheira lived in Bom Sucesso, a small town in Minas Gerais, between 1938 and 1954. He owned a great quantity of books that were preserved and thus allowed us to study the way his library was composed, what reading practices he had, as well as the speeches he made in public gatherings. The inefficiency of written communication due to high illiteracy rates was thus compensated by the work of reading orators. Júlio Castanheira utilized performance and rhetorical techniques in his speeches that were capable of constructing and accessing his readers auditory memory.